2023
DOI: 10.1111/hepr.13889
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride level and soft drink consumption predict nonalcoholic fatty liver disease in nonobese male adolescents

Abstract: Aim Differential metabolic risk factors of nonalcoholic fatty liver disease (NAFLD) in nonobese male adolescents were analyzed examining relationships between NAFLD and clinical parameters of metabolic syndrome, including exercise and soft drink consumption, in male adolescents. Methods In total, 134 male university students (nonobese, n = 78; obese, n = 56) who underwent the first‐year health checkup were divided into the NAFLD and non‐NAFLD groups based on abdominal ultrasonography (AUS) findings. Relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
1
6
1
Order By: Relevance
“…It was pointed out in a review that the risk of NAFLD increased by excess energy intake caused by the consumption of high‐fructose corn syrup, which is found in soft drinks 48 . A previous study reported that half of non‐obese NAFLD adolescents regularly consumed soft drinks 17 ; however, we found that approximately 10–20% of middle‐aged and older Japanese people were regular consumers. The changes in soft drink preference with age may be a reason why the independent association between NAFLD and soft drink consumption was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It was pointed out in a review that the risk of NAFLD increased by excess energy intake caused by the consumption of high‐fructose corn syrup, which is found in soft drinks 48 . A previous study reported that half of non‐obese NAFLD adolescents regularly consumed soft drinks 17 ; however, we found that approximately 10–20% of middle‐aged and older Japanese people were regular consumers. The changes in soft drink preference with age may be a reason why the independent association between NAFLD and soft drink consumption was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…A previous study of non‐obese Korean adults reported that the risk of NAFLD was increased in subjects who ate fast 16 . A study in Japanese non‐obese male adolescents reported that NAFLD was associated with the consumption of soft drinks 17 . Although these results suggest that dietary characteristics are independent risk factors for non‐obese NAFLD, the dietary characteristics that are key features of non‐obese NAFLD remain to be elucidated.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…45 The FIB-4 index is also powerful for the identification of advanced liver FIB in NAFLD. 7,46 In this study, CD8 þ TEMRA was an independent predictor of these three parameters in moderate-to-severe liver FIB in NAFLD, and CD8 þ TEMRA and LS value were predictors of severe liver FIB. Focused on ROC curves in severe liver FIB, as shown in Figure 3, CD8 þ TEMRA had a higher AUC value than LS value.…”
supporting
confidence: 49%
“…Several noninvasive biomarkers and predictors of NAFLD severity depending on pathological diagnosis have been reported. [5][6][7][8] We previously reported a noninvasive diagnostic method for NASH using PBMCs targeting peripheral immunity 9 ; however, immunologically, noninvasive methods to determine the association between peripheral immunity and NAFLD severity have not yet been reported. In this study, we focused on the differential patterns of peripheral memory T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%